REPRODUCTIVE PERFORMANCES OF SUMBA ONGOLE COWS INSEMINATED WITH FROZEN BELGIAN BLUE SEMEN - Riyan Nugroho Aji; Panjono Panjono; Ali Agus; Budi Prasetyo Widyobroto; Tety Hartatik; I Gede Suparta Budisatria; Ismaya Ismaya; Sigit Bintara (Buletin Peternakan, 2017)
The purpose of this study was to observe the reproductive performances of Sumba Ongole (SO) cows inseminated with frozen Belgian Blue (BB) semen. This research was expected to be used as a reference in the cow’s maintenance, especially in the implementation of Artificial Insemination (AI), as well as for subsequent studies. Parameter of this study includes the signs of estrus symptoms, S/C ratio, CR, NRR, and pregnancy time. The results showed a large value of S/C for cow SO 2.60±1.81, great value for cattle CR SO was 40%, the value of NRR was 60%, and the pregnancy time SO was 273.80±4.08. It is concluded that reproductive performance of SO cows are good, using SO cows to cross with BB cow is possible to do.